Interdisciplinary sports research as an instrument to predict the performance in competitions. (RIAF. International Journal of Physical Activity, 2023)
Sports performance consists of the interaction of individual limitations, of tasks and environmental, but research has used a mono disciplinary approach, rather than interdisciplinary, to understand performance. This study used the Football as an exemplary sport to investigate the value of an interdisciplinary approach to understand sports performance. Through this, it was also possible quantifying individual differences and designing representative tasks. Participated 59 players. Based on accessibility, the combinations of these players. They completed physiological and perceptual cognitive-motor tests. The model interdisciplinary formulated an equation that could identify the differences between the individual in the efficiency of elimination. In addition, the interdisciplinary model showed that the test of high-pressure reduced play situations more contributed in greater magnitude to the prediction of the performance of the competence than the lowest Representative Mental Toughness Index rating. In overall, this study demonstrates that a more complete understanding can be gained of sports performance, individual differences and representative tasks through through an interdisciplinary approach.
Keywords: Interdisciplinary approach; football; sports performance